Evaluation of Charge‐Regulated Supramolecular Copolymerization to Tune the Time Scale for Oxidative Disassembly of β‐Sheet Comonomers. Issue 1 (4th November 2019) - Berac, Christian M.; Zengerling, Lydia; Straβburger, David; Otter, Ronja; Urschbach, Moritz; Besenius, Pol
Abstract: A multistimuli‐responsive supramolecular copolymerization is reported. The copolymerization is driven by hydrogen bond encoded β‐sheet‐based charge co‐assembly into 1D nanorods in water, using glutamic acid or lysine residues in either of the peptide comonomers. The incorporation of methionine as hydrophobic amino acid supports β‐sheet formation, but oxidation of the thioether side‐chain to a sulfoxide functional group destabilizes the β‐sheet ordered domains and induces disassembly of the supramolecular polymers. Using H2 O2 as reactive oxygen species, the time scale and kinetics of the oxidative disassembly are probed. Compared to the charge neutral homopolymers, it is found that the oxidative disassembly of the charged ampholytic copolymers is up to two times faster and is operative at neutral pH. The strategy is therefore an important addition to the growing field of amphiphilic polythioether containing (macro)molecular building blocks, particularly in view of tuning their oxidation induced disassembly which tends to be notoriously slow and requires high concentrations of reactive oxygen species or acidic reaction media. Abstract : The supramolecular copolymerization of peptide monomers is reported, and their potential as reactive oxygen scavenger material evaluated. The incorporation of methionine as hydrophobic amino acid supports β‐sheet formation, but oxidation to methionine sulfoxide induces depolymerization. Using H2 O2, the response time of the oxidative disassembly is probed, and is found to be significantly faster in the charged copolymers compared to the neutral homopolymers.